Infant and preschooler feeding behaviors in Chinese families: A systematic review. (1st January 2022) - Guo, Shibo; Wang, Yue; Fries, Lisa R.; Li, Yilin; Zhang, Nini; Zhang, Haiyue; Wei, Haixia; Jiang, Xun; Shang, Lei
Abstract: A systematic review was conducted on the literature on feeding behaviors in Chinese families of children under 6 years old. Forty relevant publications were identified, of which 33 were published in Chinese, 7 in English. All studies were questionnaire-based and used a cross-sectional research design. Approximately half of the studies reported a score for each feeding practice/style, based on a Likert scale; the other half dichotomized these scores into a percentage of the population that reported frequent use of the behaviors. The most commonly reported feeding style of Chinese caregivers was a locally defined "active response" style that somewhat resembled authoritative parenting. The most commonly reported feeding practices were praise, encouraging trying new foods, encouragement of balanced diet and encouragement of healthy eating. Some behaviors showed a great deal of variance in prevalence between studies, which may be at least partially due to differences in methodology and how behaviors were defined. Some feeding behaviors varied in frequency depending on the child's age, although longitudinal studies are needed to better understand how these evolve over time. Child body composition was also associated with feeding behaviors use, although the direction of the association cannot be determined due to the cross-sectional nature of the research. There is still an important gap in the literature regarding the feeding behaviors of non-maternal caregivers, as grandparents often play an important role in childcare in China.